Factors Determining Stock Prices: Financial Performance Perspectives and Management Strategy - Mukhsin, Muhammad; Lukiana, Ninik; Prasetyo, Aji (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The purpose of this research is to investigate the extent to which financial indicators and managerial policies affect stock valuations among consumer goods sector firms listed on the Indonesia Stock Exchange (IDX) over the 2018 to 2022 period. The variables analyzed include Debt to Equity Ratio (DER), Return on Equity (ROE), Current Ratio (CR), Price to Earnings Ratio (PER), Firm Size, and Dividend Payout Ratio (DPR). This study uses multiple linear regression methods to test the relationships between variables. The results showed that DER, ROE, Firm Size, and DPR had a significant effect on stock prices, while CR and PER had no significant effect. In theory, variables such as ROE and firm size reflect the company's managerial performance and stability, which are the main considerations for investors. The practical implications of this study provide guidance for investors to focus on these variables in investment decision-making. Meanwhile, companies need to pay attention to their capital structure and dividend policy to attract investor interest and increase the attractiveness of stocks in the market.